Comparisons of oxbow lake fish assemblages in relation to bigheaded carp establishment in the lower White River, Arkansas - Eggleton, Michael A.; Salzmann, Cody J.; Kaiser, Joseph E.; Smith, Shannon C. F. (Ecological processes, 2024)
Background Since the late 1990s, bigheaded carps (largely silver carp [ Hypophthalmichthys molitrix ] but also bighead carp [ H. nobilis ]) have established throughout the lower Mississippi River basin. Using previously studied oxbow lakes in the lower White River basin, Arkansas, we compared current (2017, “post-carp” establishment) fish assemblages to historical (2002, “pre-carp” establishment) fish assemblages. Fish assemblages were comprehensively assessed using multiple gears, including boat electrofishing, mini-fyke nets, and experimental small-mesh gill nets. Results T -tests suggested that fish assemblage indices of richness, diversity, evenness, and dominance were often greater ( P < 0.05) during the post-carp period as reflected by boat electrofishing and experimental gill nets. However, all indices were generally similar ( P > 0.05) between the pre-carp and post-carp period with fish assemblages depicted using mini-fyke nets. Nonmetric multidimensional scaling analyses indicated that fish assemblages differed structurally between pre-carp and post-carp periods. Assemblage differences were linked to both small and large abundance changes for more than 20 species. Abundances of gizzard shad ( Dorosoma cepedianum ), emerald shiner ( Notropis atherinoides ), pugnose minnow ( Opsopoeodus emiliae ), crappies ( Pomoxis spp.), bluegill ( Lepomis macrochirus ), orangespotted sunfish ( L. humilis ), and yellow bass ( Morone mississippiensis ) declined between the pre-carp and post-carp periods. Conversely, abundances of weed shiner ( N. texanus ), pallid shiner ( Hybopsis amnis ), longear sunfish ( L. megalotis ), buffalofishes ( Ictiobus spp.), and gars ( Lepisosteus spp.) generally increased during the same period. Conclusions Although not possible to conclude assemblage shifts were entirely related to bigheaded carps due to the absence of an appropriate reference system where carps did not establish, the wide establishment of these carps is one of the most pervasive changes to have occurred in the lower White River ecosystem during the past two decades. Thus, it is probable to conclude that post-carp establishment observations from this study were at least, in part, attributable to bigheaded carp establishment. Impacts of further range expansions by bigheaded carps in the White River and other lower Mississippi River sub-basins are unclear, though this study suggests probable effects on native fish assemblages, underscoring the need for further research and monitoring.